2012
DOI: 10.1111/j.1365-2486.2012.02765.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal sea ice cover as principal driver of spatial and temporal variation in depth extension and annual production of kelp in Greenland

Abstract: We studied the depth distribution and production of kelp along the Greenland coast spanning Arctic to sub-Arctic conditions from 78 °N to 64 °N. This covers a wide range of sea ice conditions and water temperatures, with those presently realized in the south likely to move northwards in a warmer future. Kelp forests occurred along the entire latitudinal range, and their depth extension and production increased southwards presumably in response to longer annual ice-free periods and higher water temperature. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
118
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(139 citation statements)
references
References 57 publications
10
118
1
Order By: Relevance
“…Increased nutrient input associated with warming could have been a source of enhanced growth, but a recent nutrient enrichment study shows that macroalgae in Kongsfjord are not N-limited because they take up and store nitrogen compounds during winter (32). Along the rocky coastlines of the Arctic, boreal macroalgae are predicted to expand within the 21st century as a consequence of climate warming (21,33), an expectation that our findings support.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Increased nutrient input associated with warming could have been a source of enhanced growth, but a recent nutrient enrichment study shows that macroalgae in Kongsfjord are not N-limited because they take up and store nitrogen compounds during winter (32). Along the rocky coastlines of the Arctic, boreal macroalgae are predicted to expand within the 21st century as a consequence of climate warming (21,33), an expectation that our findings support.…”
supporting
confidence: 75%
“…The observed increase in macroalgal cover is likely representative of a regional trend toward increased macroalgal biomass, as supported by a separate study in Hornsund, in the south of Svalbard, where a threefold increase in biomass was recorded between 1988 and 2008 (20). In addition, a study from West Greenland documented substantial increases in the productivity and depth extension of macroalgae (kelp beds) in relation to the retreat of sea ice and prolonging of the open water period (21). In our study, the character of the observed structural and functional change in the benthos, in both investigated fjords, is indicative of an abrupt ecological regime shift (8).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In addition to favoring the poleward flux of species, arctic warming will likely affect their metabolic rates (Brown et al, 2004), increasing photosynthetic rates and growth and affecting their phenology, with an earlier initiation of growth and a longer season to complete their growth cycle (Kortsch et al, 2012;Krause-Jensen et al, 2012;Clausen et al, 2014;Olesen et al, 2014). Moreover, future increases in atmospheric CO 2 , and airsea supply of CO 2 may further propel macrophyte expansion in arctic waters.…”
Section: Macrophyte-dominated Ecosystems In a Warmer Arcticmentioning
confidence: 99%
“…Hence, the Arctic Ocean contains a vast potential habitat for marine macrophytes. However, much of this potential habitat is unlikely to be occupied at present because it is permanently covered by ice, impacted by ice scouring or because dense ice cover limits the duration of the growth period (Müller et al, 2009;Kortsch et al, 2012;Krause-Jensen et al, 2012).…”
Section: Macrophyte-dominated Ecosystems In a Warmer Arcticmentioning
confidence: 99%